Reliability Perspective on Nano-silver Sinteringin SiC Power Modules for Space Applications - Xiaoqi Li; Lei Wang; Chenshan Gao; Wenbo Wang (Space: Science & Technology)
In the field of aerospace, power electronics have a broad range of applications. The advent of SiC power devices could markedly improve the performance of existing systems and enable new applications. However, this potential cannot be fully realized if SiC dies are packaged with conventional materials and processes that limit performance in areas such as maximum operating temperature and parasitic elements. More importantly, the reliability of SiC device interconnection is also influenced by packaging technology. Compared to solder material, nano-silver sintering offers several advantages: its thermal conductivity is higher than that of solder, and its melting point of 960 °C is markedly greater than that of solder. Additionally, the electromigration rate of nano-silver is typically 1 to 2 orders of magnitude lower than that of solder. These advantages result in superior electrical and thermal performance, as well as enhanced reliability for silicon carbide power modules. This paper provides an overview of nano-silver sintering technology from the perspective of reliability, summarizing considerations for more reliable materials and processes. It also assesses long-term reliability by investigating failure modes observed in standard tests and applications of sintered joints. Challenges and prospects of using this technology in space applications are also discussed.